Effects of decabromodiphenyl ether (BDE-209) on a mangrove plant, Kandelia obovata and the uptake, translocation and accumulation of BDE-209 - Wang, Ying; Du, Yi-Tong; Tam, Nora Fung-Yee (Frontiers in Marine Science, 2022)
Due to close proximity to urban development, mangroves exposed to the contamination of polybrominated diphenyl ethers (PBDEs). Decabromodiphenyl ether (BDE-209) is one of the most predominant PBDE congener. The present study aimed to investigate the toxic effects of BDE-209 on the antioxidative and non-antioxidative responses of Kandelia obovata, a very common mangrove species, under different concentrations of BDE-209, 0.1, 1, 5 and 10 mg l-1. BDE-209 did not exhibit any negative effects on the growth of K. obovata seedlings. The stimulatory effects of BDE-209 on the enzymes including superoxide dismutase, peroxidase and catalase only occurred in weeks 1 and 4 and diminished in week 8. The concentrations of total polyphenols (TP) and extractable condensed tannins (ECT) were not affected by BDE-209. The production of O2·- was induced only at the very high level of BDE-209 (10 mg l-1). H2O2 was induced only in weeks 1 and 4 under BDE-209 treatment. BDE-209 was taken up by the roots of K. obovata, translocated to above-ground tissues, and accumulated in plant tissues with the concentrations declined in the order of root > propagule > stem > leaf. Although BDE-209 has higher molecular weight and higher log Kow than other PBDE congeners, the K. obovata seedlings could absorb, translocate and accumulate BDE-209. These findings suggested that mangrove plants could take up, accumulate PBDEs, and BDE-209 are less toxic than other congeners but more difficult to be removed by mangrove systems.